Robert Therrien. - Bryson, Norman; Frick, Thomas; Rich, Andrea L.; Zelevansky, Lynn; Museum of Art, Los Angeles; Site Santa Fé; Contemporary Art Museum, Houston; Museo deArte Contemporaneo, Monterrey (Los Angeles : LACMA (Los Angeles County Museum of Art), 2000)
The Artwork of Robert Therrien is defined by contradictions. Occupying an ambiguous zone between abstraction and figuration, it is extremely refined and formalized, yet his objects and images also make reference to commonplace, even clichéd motifs - a snowman, a cloud, a Dutch door, a bird in flight, a stack of plates. In the perfection of their proportions and the simplicity of their forms these works - sculptures, reliefs, and two-dimensional pieces - partake of a cool objectivity. Their narrative associations, however, give them the intimacy of personal history. They possess a wholesome familiarity, yet their often huge size gives them an uncanny, disquieting quality. In this volume, which accompanies the exhibition Robert Therrien and examines the artist's works of the past decade, curator Lynn Zelevansky explores the transformation of forms that has been the hallmark of Therrien's artistic process and situates his work within contemporary art practice. Essayist Thomas Frick discusses the work vis-à-vis the formalist tradition in art and examines the paradoxical nature of its abstract and figurative aspects. In the volume's third and final essay art historian Norman Bryson investigates the visceral effect of Therrien's sculpture on the viewer, relating its effects to the corporeal invasions and restitutions found in animated cartoons. Therrien has exhibited only rarely, and there has been relatively little substantial writing about his art. Robert Therrien is the most comprehensive publication to date on the unique work of this imoortant contemporary artist.
Checklist p. 98-99, tent. p. 100-101, bibliog. p. 102-105
Engels
Robert Therrien, Museum of Art, Los Angeles, February 20- May 7, 2000 / SITE Santa Fe, June 17 - September 10, 2000 / Contemporary Art Museum, Houston, December 16, 2000 - February 28, 2001 / Museo deArte Contemporaneo, Monterrey, March-June 2001
boek
Keywords: Therrien, Robert